2021
DOI: 10.3390/cells10061463
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rho-Associated Kinase Inhibitor and Mesenchymal Stem Cell-Derived Conditioned Medium on Corneal Endothelial Cell Senescence and Proliferation

Abstract: This study aims to obtain sufficient corneal endothelial cells for regenerative application. We examined the combinatory effects of Rho-associated kinase (ROCK) inhibitor Y-27632 and mesenchymal stem cell-derived conditioned medium (MSC-CM) on the proliferation and senescence of rabbit corneal endothelial cells (rCECs). rCECs were cultured in a control medium, a control medium mixed with either Y-27632 or MSC-CM, and a combinatory medium containing Y-27632 and MSC-CM. Cells were analyzed for morphology, cell s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…In contrast, cell cycle checkpoint genes such as CDC25C, CDCA2 and CIP2A did not vary in the combinatory medium but were significantly downregulated in either the ROCK inhibitor or MSC-CM alone. These results demonstrated that the synergistic effect of Y-27632 and MSC-CM on corneal endothelial cell proliferation and senescence could represent a significative potential intervention for the regeneration of human corneal endothelial tissue [3].…”
mentioning
confidence: 71%
“…In contrast, cell cycle checkpoint genes such as CDC25C, CDCA2 and CIP2A did not vary in the combinatory medium but were significantly downregulated in either the ROCK inhibitor or MSC-CM alone. These results demonstrated that the synergistic effect of Y-27632 and MSC-CM on corneal endothelial cell proliferation and senescence could represent a significative potential intervention for the regeneration of human corneal endothelial tissue [3].…”
mentioning
confidence: 71%
“…In all patients the procedure was combined with rho-associated protein kinase inhibitor (ROCKi) adjunctive therapy, which had previously been shown to promote CEC adhesion, prevent apoptosis, increase cell proliferation, restore cell morphology and function, and overall improve engraftment. [44–47]…”
Section: Endotheliummentioning
confidence: 99%
“…In all patients the procedure was combined with rho-associated protein kinase inhibitor (ROCKi) adjunctive therapy, which had previously been shown to promote CEC adhesion, prevent apoptosis, increase cell proliferation, restore cell morphology and function, and overall improve engraftment. [44][45][46][47] Recently, 5-year follow-up for these patients was published [48 && ]. Ten of the 11 eyes demonstrated improvement in endothelial cell density (ECD), central corneal thickness (CCT) and BCVA.…”
Section: Endotheliummentioning
confidence: 99%
“…A dual-media approach with alternating stabilisation (low-mitogenic) and proliferation (high mitogenic) conditions has been shown to be effective [25,44,45]. More recently, human platelet lysate (HPL) [46][47][48][49], small molecules [50,51] and mesenchymal stem cell derived conditioned media [52,53] have been reported to be helpful.…”
Section: Corneal Endothelial Cell Culture Protocolmentioning
confidence: 99%